2018
DOI: 10.1055/s-0038-1675330
|View full text |Cite
|
Sign up to set email alerts
|

Does the RAM Cannula Provide Continuous Positive Airway Pressure as Effectively as the Hudson Prongs in Preterm Neonates?

Abstract: Objective To compare the level of continuous positive airway pressure (CPAP) delivered by the RAM cannula system (Neotech, Valencia, CA) with that delivered by a traditional CPAP nasal delivery interface (Hudson prongs; Hudson-RCI, Temecula, CA) in preterm infants with respiratory distress. Methods This was a crossover intervention study in a convenience sample of preterm infants with respiratory distress requiring treatment with CPAP. We measured the mean intraoral (pharyngeal) pressure, which app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 16 publications
4
34
1
Order By: Relevance
“…19 Recent evaluation of pharyngeal pressures with the RAM cannula demonstrated a decrease in the pressure of up to 2.45 cmH 2 O compared with an increase of 0.40 cmH 2 O with the SBP prongs. 17 The increases in the transmission pressures with the larger RAM cannulas (newborn and infant) in our in vitro studies are consistent with the decreasing resistance in the RAM tubing found on their FDA-approved data (www. neotechproducts.com).…”
Section: Discussionsupporting
confidence: 88%
“…19 Recent evaluation of pharyngeal pressures with the RAM cannula demonstrated a decrease in the pressure of up to 2.45 cmH 2 O compared with an increase of 0.40 cmH 2 O with the SBP prongs. 17 The increases in the transmission pressures with the larger RAM cannulas (newborn and infant) in our in vitro studies are consistent with the decreasing resistance in the RAM tubing found on their FDA-approved data (www. neotechproducts.com).…”
Section: Discussionsupporting
confidence: 88%
“…However, in the absence of an analog recording of pressure waveform, we recorded displayed digital values and calculated mean of these values to quantify delivered pressures with each nasal interface.To the best of our knowledge, this is the first study comparing delivered oropharyngeal CPAP with three different commonly used nasal interfaces. Similar to the results of our study, Gerdes et al7 and Singh et al6 also found that delivered oropharyngeal pressures were significantly less than the set CPAP with the use of RAM cannula. However, in the study by Singh et al6 delivered in vivo pressures were measured by closing the mouth which may not actually simulate the CPAP delivery method at many centers where active closure of mouth for CPAP delivery is not practiced.…”
supporting
confidence: 91%
“…[11][12][13][14] Many factors affect the actual delivered pressure when applying nasal CPAP including nasal interface, bias flow, leak around the nose, and leak from the mouth. 7,[11][12][13][14][15][16] Type of nasal interface is one of Singh et al 6 in their study reported higher delivered mean pressures than the set pressures with the use of Hudson prongs, whereas, in our study, the mean delivered pressure with Hudson prongs were 0.9 and 0.8 cm H 2 O less than the set CPAP of 5 and 6 cm H 2 O, respectively. The use of different flow rates and closure of the mouth during pressure recordings may be the reasons for the observed differences in the studies.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Several other interfaces are widely used for CPAP treatment. The RAM cannula interface has been used for providing CPAP and nasal intermittent positive pressure ventilation 23–26. This is not Food and Drug Administration approved, and the use is off-label.…”
Section: Discussionmentioning
confidence: 99%